The limitations of today's clinical guidance: Atypical femoral fracture and long-term bone-modifying agents in the oncology setting. (July 2020) - Cheung, Edna; Borno, Hala T
While bone-modifying agents such as bisphosphonates and denosumab are crucial to preventing skeletal-related events in patients with bone metastases, the optimal duration remains undefined. Extended duration may be associated with adverse effects such as osteonecrosis of the jaw and atypical femoral fracture. Although uncommon, atypical femoral fracture represents a serious consequence of prolonged bone-modifying agent use and are characterized by a prodrome and distinct radiographic findings. The oncology setting encompasses a unique set of atypical femoral fracture risk factors and considerations, with hormonal therapy in early stage disease, bone metastases in the advanced setting, and new targeted agents that may affect bone homeostasis. As outcomes in cancer treatment continue to improve, the questions of risks versus benefits of long-term bone-modifying agents and how to mitigate atypical femoral fracture risk become increasingly pertinent.